2007
DOI: 10.1038/sj.bjc.6603768
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the anti-apoptotic function of survivin-ΔEx3 during TNFα−mediated cell death

Abstract: Survivin is an oncogenic protein involved in cell division and acts as an anti-apoptotic factor. It is highly expressed in most cancers and is associated with chemotherapy resistance, increased tumour recurrence, and shorter patient survival. This makes anti-survivin therapy an attractive cancer treatment strategy. These functions are mediated by several survivin spliced variants, whose expression may correlate with cancer progression. One of the spliced variants, survivin-DEx3, is known to inhibit apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Moreover, it is known to be overexpressed and related with more aggressive behavior, increased tumor recurrence, chemotherapy resistance, increased survival in various tumors [3][4][5][6][10][11][12][13][14][15]. In TC, Haghpanah et al reported the significantly higher survivin expression in TC than in follicular adenoma, and Ito et al reported the significant link between survivin expression and the dedifferentiation of TC [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is known to be overexpressed and related with more aggressive behavior, increased tumor recurrence, chemotherapy resistance, increased survival in various tumors [3][4][5][6][10][11][12][13][14][15]. In TC, Haghpanah et al reported the significantly higher survivin expression in TC than in follicular adenoma, and Ito et al reported the significant link between survivin expression and the dedifferentiation of TC [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Survivin expression correlates with resistance to apoptosis induced by a number of chemotherapeutic agents [33,70,71] as well as death inducers such as Fas, TRAIL, TNF , etc [70][71][72][73][74][75][76][77]. Consistent with its anti-apoptotic role, Survivin localizes to the cytoplasm where it interacts with caspase 3 [70].…”
Section: Inhibition Of Apoptosis By Survivin and Its Splice Variantsmentioning
confidence: 92%
“…Survivin is a protein that is cell cycle-regulated with a robust increase in the G2/M phase in cancer cells (12,13). Survivin is known to be overexpressed and related with more aggressive behavior, increased tumor recurrence, chemotherapy resistance and increased survival in various tumors (6,(14)(15)(16)(17)(18)(19)(20)(21). As a prognostic factor, survivin expression is significantly associated with a poor clinical outcome in certain types of cancer, including liver (2), colorectal and breast (3,6).…”
Section: Discussionmentioning
confidence: 99%